Otoryye popytayutsya napast' na nassu stranu, - poluchat sokrushitel'nyy otpor, chtoby adno bylo im sovat' svoye svinoye pylo v nash sovetskiy ogorod (ОГИЗ - ИЗОГИЗ (Izogiz), 1936)
Rows of Red Army soldiers bristling with bayonets and cannon facing off against pig wearing Nazi hip-sword Original title: Оторые попытаются напасть на нассу страну, - получать сокрушительный отпор, чтобы адно было им совать своё свиное пило в наш советский огород. Suggested translation: They will try to attack our country, they will receive a crushing rebuff, so that it would be inconvenient for them to poke their pigs into our Soviet garden PO-0030